Identifikasi Tingkat Aplikasi Teknologi Petani Padi Sawah Lebak Di Kabupaten Ogan Ilir Sumatera Selatan - Chuzaimah Chuzaimah; Ahmad Febriyansyah (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2016)
Chuzaimah, et al.Â Rice Farmers Technology Applications Swamp PaddyÂ in the Distric Ogan Ilir Sumatera Selatan. JLSO 5(2):127-136.Lowland swamp land development for agriculture, especially food crops on a large scale requires land arrangement and the network of water management and the application of technologies appropriate to local conditions in order to obtain maximum results. The purpose of this study was to analyze the swampy lowland rice technology applications, revenues and relationships both in Ogan Ilir. This study was conducted in Ogan Ilir District of South Pemulutan Cahaya Marga village. Sampling method in using Simple Random Sampling, by taking 30 farmers. Data collected consist of primary and secondary. This study was analyzed by using Likert scaling technique. The results showed that application of high technology swampy rice paddy where the average application of technology in Desa Cahaya Marga is 19.23 which is the recommended. For each application technology swampy lowland rice fertilization has not seen only as recommended. Additionally pest and disease control in the application of technology swampy rice paddy in the village of Light Marga has not as directed seen from the scores just 2.13. The amount of household income of farmers in Desa Cahaya Marga is Rp 9,845,591 cultivated area per planting season per year, while total household income of farmers in Desa Cahaya Marga is Rp 20,593,336 per year. Simultaneously Application technology (X) significantly affects the productivity of lowland rice paddy (Y) where Fhit = 0.79 to be significant at the level Î± = 0.05 (5%), even at the 1% significance level, there is a positive relationship between the application of technology Â with revenues.